PPLICATION OF THE STAD TYPE COOPERATIVE LEARNING MODEL TO IMPROVE STUDENT LEARNING ON THE INDONESIAN FOREIGN POLITICS TOPIC IN CLASS VI OF SD NEGERI ROTTEUNGOH - Afriansyah; Siti Mayang Sari; Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research aims to analyze the improvement in student learning outcomes after implementing the STAD type cooperative learning model on topic Indonesian Foreign Politics in class VI SD Negeri Rotteungoh. This research was classroom action research consisting of two cycles. Each cycle had four stages, namely: planning, implementation, observation, and reflection. The research was carried out at SD Negeri Rotteungoh, Meukek District, South Aceh Regency for 3 months in the even semester of the 2022/2023 academic year. The subjects of this research were 22 class VI students consisting of 12 male students and 10 female students. The instruments used were formative tests and observation sheets. Data analysis used descriptive statistics based on the results of formative tests and observation sheets for each cycle. The research results showed that student learning outcomes increased from cycle I to cycle II, namely cycle I (68.18%) and cycle II (90.91%). The STAD type cooperative learning model motivates students to convey ideas and questions so that student learning outcomes increase. The STAD type cooperative learning model can be used as an alternative learning material for Indonesian foreign policy topicbecause it can improve student learning outcome